2008
DOI: 10.1007/s10826-008-9249-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Parental Rearing Styles and Child Behaviour Problems among Portuguese School-Aged Children

Abstract: The majority of studies investigating the effects of parental behaviour on the child's adjustment have a dimensional approach. We identified the existence of various patterns in parental rearing styles and analysed the relationship between different parenting patterns and behavioural problems in a group of school-aged children. A longitudinal, multi-informant study was conducted. The sample consisted of 519 school-aged children from the Portuguese general population. Parental rearing styles were measured using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
2
42
0
4
Order By: Relevance
“…The studies that assessed their own reliability reported internal consistency using Cronbach's alpha (Cronbach, 1951). Test-retest correlations were reported in three studies (Aunola & Nurmi 2005;Stevens et al, 2007;Pereira et al, 2009). Kuder-Richardson 20 (K -R 20) coefficient and Split-half reliability (Spearman-Brown) were reported in study of Aunola and Nurmi (2005).…”
Section: N= 855excludedmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies that assessed their own reliability reported internal consistency using Cronbach's alpha (Cronbach, 1951). Test-retest correlations were reported in three studies (Aunola & Nurmi 2005;Stevens et al, 2007;Pereira et al, 2009). Kuder-Richardson 20 (K -R 20) coefficient and Split-half reliability (Spearman-Brown) were reported in study of Aunola and Nurmi (2005).…”
Section: N= 855excludedmentioning
confidence: 99%
“…High levels of parental rejection, over protection and excessive control have similarly been found to be positively associated with children's behavioural problems. In contrast these relationships were reported to be negative when parents displayed high levels of behavioural control (i.e., monitoring or awareness of their children) and emotional warmth and support (Barber et al, 1994;Berkien et al, 2012;Pereira et al, 2009). Moreover, Aunola and Nurmi (2005) showed that children's external problems tend to be reduced through a combination of high levels of behavioural control and low levels of psychological control.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Children and adolescents were examined separately in the analyses to explore possible age differences for several reasons: 1) these two phases have different specificities regarding their developmental tasks and so should be considered separately in research (Holmbeck, 2002); 2) Wallander and Varni (1998) reinforce the need to implement a developmental perspective in research on individual and family adjustments to pediatric chronic conditions since youth and their families are in continuous development (Wallander, Thompson, & Alriksson-Schmidt, 2003); 3) finding differences between children and adolescents may help tailor more specific intervention programs for pediatric obesity; 4) adolescents often experience developmental changes that might impact the behaviors of significant others (e.g., mothers' behaviors; Holmbeck, 2002); 5) research has found developmental differences in psychosocial functioning (e.g., Swallen, Reither, Haas, & Meier, 2005); finally, 6) children and adolescents rely on parents differently not only in relation to eating and physical patterns but also in general health guidance, but, younger children may demand more of caregivers and require more supervision (Pereira, Canavarro, Cardoso, & Mendonça, 2009) and adolescents have more autonomy (Erikson, 1982) which may be reflected, for instance, in the use of different parenting styles (Frontini, Moreira, & Canavarro, 2016). By examining the role of age, this study will provide a more comprehensive understanding of the variables at different developmental stages.…”
Section: The Current Studymentioning
confidence: 99%
“…Estes dados estão em consonância com as conclusões de vários estudos, segundo as quais os estilos educativos parentais que recorrem mais à rejeição estão associados a uma maior frequência de resultados desenvolvimentais negativos, designadamente a um apego mais inseguro (Brown & Whiteside, 2008;Pereira, Canavarro, Cardoso, & Mendonça, 2009). No mesmo sentido, os estudos que utilizam o EMBU para avaliar a perceção do comportamento parental também têm descrito uma associação entre o apego inseguro e níveis mais elevados de rejeição parental, e, em oposição, níveis mais baixos de suporte/afeto parental (Muris et al, 2000;Muris et al, 2003).…”
Section: Discussão E Conclusõesunclassified